TÜRKİYE - Ilknur Yücel; Nadiye Camci (Health and Technology Journal (HTechJ), 2024)
This study was conducted to examine nursing graduate thesis studies in order to evaluate the effect of professional care provided by nursing professionals on the quality of life of individuals in Turkey. In this study, master's and doctoral theses registered in the archive of the Thesis Center of the Council of Higher Education were examined, and a scan was made with the words "nursing" and "quality of life". As a result of the screening, a total of 10 studies were reached between 2010 and 2022. This study was carried out on 4 thesis studies in which nursing care, which meets the inclusion criteria, is at the forefront. All 4 of the theses are master's theses. The first of the studies  was to determine the effect of nurse education on dyspnea, fatigue and quality of life in patients with heart failure, the second was  to determine the relationship between the level  of depression and quality of life of individuals with Acute Coronary Syndrome, and the third was the effect of planned nursing education on quality of life, anxiety and depression in patients with Chronic Obstructive Pulmonary Disease (COPD) In order to evaluate, the fourth was conducted to evaluate the quality of life and perception of nursing care of oncology patients admitted to the emergency department. In the studies, it was determined that the quality of life was effective with the nursing care provided. In line with the findings obtained, it is recommended to develop nursing care plans to increase the quality of life, since a relationship has been determined between quality of life and signs and symptoms of the disease.